Effect of Green Human Resource on Achieving Sustainable Development According to International Standard (ISO 20121: 2012) A Case Study at the Center for Disease and Kidney Transplantation / Department of Medicine City - Bushra Hashim Mohammad; Mohammad Abadi Hammod (Journal of Madenat Alelem University College, 2021)
The aim of this research is to test the correlation and regression between the green human resource as an independent explanatory variable in its dimensions (analysis and design of green jobs, green human resource planning, green employment, green wages and incentives, green performance assessment, green training and development,) And sustainable development in accordance with the requirements of ISO20121: 2012 as a responsive variable in its main components which included the organization context, leadership, planning, support, operations, performance evaluation, improvement). The problem of the study was the absence of sufficient environmental awareness in the human resources working in the organization under consideration, which negatively affects the achievement of sustainable development according to the requirements of the standard in research. The practical side of the study was completed in the Department of Medicine City / Center for Diseases and Kidney Transplantation. In order to obtain the necessary data and information, the search list was based on the collection of data and information on the indicators of green human resources and the provisions of( ISO 2012: 2012), The use of a set of statistical methods in the analysis of data represented by the weighted arithmetic mean, and the percentage of conformity to diagnose the gap between indicators of green human resources and the application of the provisions of the International Standard (ISO 20121: 2012) And the actual reality of each of them. The simple linear regression coefficient, correlation coefficient, In order to test the hypotheses and their significance among the variables of the study, the research reached a number of conclusions. The most important of which is the existence of an essential correlation and the significant effect of the green human resource in achieving sustainable development in accordance with ISO 2012: 2012.